Pengaruh Terapi Ultrasound Terhadap Lemak Subcutaneus Pada Perut - Puspitasaru, Silvia Febrieni, Dwi Rosella Komalasari,SST.FT.,M.FIS., DIPL.CIDESCO, Yulisna Mutia Sari, S.ST. FT., Msc (GRS) (2015)
Subcutaneus fat is fat that located in under the skin, and usually appear from out of body, especially if the numbers are exaggerated. The location of subcutaneus fat in stomach area, thigh, waist and arm. Fat in the body come from fat it self and carbohydrates are destroyed be glucose and triagliserol (carbohydrates that saved) in subcutan layer. Ultrasound therapy is a therapy used the mechanical vibrations of sound waves with frequency more than 20.000 Hz, however usually used is 0,5-5 MHz. Population in the research is 20 people from S1 students of Physiotherapy 2011 with 3 people as the sample. This research is research quasi experimental and use single-case research as the method of this research with descriptive analytic design, free fat reduction variables subcutan and variables bound of ultrasound therapy. Three respondences would therapy for 30 minutes with 8 times therapy for a month. Exposure results in this study were made in the form of data description, namely in the form of results : subcutan fat that measured using skinfold calipers served in graphic form will measured overy research to each respondences. The results of this research showed that decrease of fat from three respondences, each of the respondences has decrease of 3,85%, 3,01% and 2,44%. The conclusions from this research is there is effect of ultrasound therapy against subcutaneus fat in stomach. Keywords : Subcutaneus fat, Ultrasound, skinfold calipers.